Culloden - Sked, Phil; Illustrated by Proudfoot, Jim (Edinburgh National Trust for Scotland, 1990)
For years the legend of Bonnie Prince Charlie and the black memory of Butcher Cumberland have blossomed side by side. Here, from memoirs, letters, newspapers and regimental order books, the author reconstructs the battle and the months that followed.
Include Collour Illustrations
Designed by Boyter, Ian
Keywords: Scotland -- Culloden, Battle of (Scotland : 1746) -- Jacobite Rebellion (1745-1746)